Legal Analysis Of The Balance Between Workes Rights And Obligations Based On Law No. 13 Of 2003 - Wisudawan Katjong , Rizky; Revie Kurnia Katjong (Al-Zayn: Jurnal Ilmu Sosial, Hukum & Politik, 2025)
The legal relationship between workers and employers in Indonesia still faces normative imbalances due to the dominance of legal-formal approaches in regulating labor rights and obligations. Although Law No. 13 of 2003 guarantees the right to strike as a fundamental labor right, its implementation is obstructed by stringent administrative procedures and restrictive legal interpretations that limit workers’ room for advocacy. This study aims to analyze the normative and positive legal constructions of the balance between workers’ rights and obligations, using a qualitative approach and normative juridical method by examining legislation, legal doctrines, and court rulings. The findings indicate that employers are granted broader discretion in executing lockouts compared to the procedural burden placed on workers to conduct lawful strikes, thereby creating structural inequality legitimized by positive law. The implications of this research highlight the urgency of reformulating labor law to ensure a more just, balanced, and structurally aware framework, allowing the law to serve as an instrument of social emancipation rather than a mechanism of procedural repression